Clinical usefulness of venlafaxine in the context of common comorbidities of depression and neurotic disorders - Kokoszka, Andrzej (Przewodnik Lekarza/Guide for GPs, 2005)
The concise review of literature on venlafaxine, comorbidities of depression and neurotic disorders as well as application of venlafaxine in the treatment of other disorders, than depression is presented. The generalized anxiety disorder and social phobia, i. e., the most often comorbidies of depression, that can be trea- ted with venlafaxine, are described.